PENGARUH METODE EKSPERIMEN DALAM IPA TERHADAP HASIL BELAJAR SISWA KELAS IV SD PONTIANAK TIMUR - Fatimah, Syarifah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This recearch aims to determine how much influence the use of experimental modes on learning Natural Science on student learning outcomes fourth grade SDN 05 Pontianak East. The method used in this research is experimental method with pre experimental design, with one group pre-test and post-test design. The subjects were 28 students consisting of 2 males and 8 females. Data collection tool used in the form of test questions formed multiple choice with the number of 25 questions. The results showed the average of student learning outcomes of 73.28. The result of hypothesis (t-test) obtained t counted 9,23 with db = 28 -1 = 27 with significant level (Î±) = 5% obtained ttable equal to 1,703 Because t count equal to 9,23> ttable equal to 1,703 hence hypothesis expressed accepted. This means that there are differences in student learning outcomes before using experimental learning methods with student learning outcomes after using the experimental method. From the calculation effect size (ES), obtained 1.47 (high criteria). This means that the experimental method gives a high influence on the learning outcomes of Natural Science grade IV Pontianak East Elementary School. Keywords: Experiment Method, Student Learning Outcomes,